Yemeni Pre-Service Teachers Educators’ Perceptions of Lesson Study in Pre-service Teachers Preparation Program (an Exploratory Study) - Al-hadabi, Abdulsalam Sulaiman Dawood (Journal of Educational and Psychological Sciences, 2019)
Lesson study (LS), as a model for improving teaching and learning, has tremendous merits for both teachers and students during learning-teaching procedures. Thus, this study can serve in developing an awareness of the pre-service teachers’ educators (PSTEs) toward LS as a collaborative professional development model. This study, therefore, aimed to explore the perception of participants who were selected purposively (i.e. using a purposive sample) from the PSTEs at faculty of education-Amran university, Yemen, about LS and its implementation (LSIs). To this end, an open-ended interview was conducted with six interviewees, participants mentioned above, in the second semester of the academic year (2017/2018s). The most important result of this study was that all of the PSTEs participated in this study were not aware about the LS and LSIs, too. Based on the study’s results, some recommendations were recommended.